Mandarin language offered to industries at UMP aimed at enhancing professionalism - Yong, Ying Mei (2018)
Universiti Malaysia Pahang (UMP) is now offering Industrial Mandarin language to industrial workers aimed at enhancing their skills and is organised by its Mandarin Language and Cultural Centre (MLCC).